2007
DOI: 10.1007/s10393-007-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response of the Tasmanian Devil (Sarcophilus harrisii) and Devil Facial Tumour Disease

Abstract: One of the most remarkable aspects of Devil Facial Tumour Disease (DFTD) is its infectious nature, and for successful transmission it must avoid detection by the devil's immune system. For this to occur, the devil either is severely immunosuppressed or factors produced by the tumor contribute to its avoidance of immune detection. An analysis of the devil's immune system revealed the presence of normal-looking lymphoid organs and lymphoid cells. At a functional level the lymphocytes proliferated in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 17 publications
(20 reference statements)
2
58
0
Order By: Relevance
“…Developing vaccines for pathogens that affect only wildlife is likely to be prohibitively expensive in most cases. There has been research into developing a vaccine for DFTD [114,115], but it has yet to result in an effective vaccine.…”
Section: (A) Isolating Infected Populationsmentioning
confidence: 99%
“…Developing vaccines for pathogens that affect only wildlife is likely to be prohibitively expensive in most cases. There has been research into developing a vaccine for DFTD [114,115], but it has yet to result in an effective vaccine.…”
Section: (A) Isolating Infected Populationsmentioning
confidence: 99%
“…Siddle et al (2007a) confirmed that MHC class I and II genes are expressed in DFTD tumors at the mRNA level, although further studies are required to determine whether MHC genes in DFTD are correctly translated, trafficked and displayed (Table 1). The lack of diversity at MHC loci, coupled with weak responses of east coast devils to allogeneic mixed lymphocyte culture, has led to the suggestion that this population may be functionally identical at MHC loci, thus permitting the spread of DFTD as an allograft ( Figure 2; Woods et al, 2007;Siddle et al, 2007a;Kreiss et al, 2008). However, as other marsupials have been reported to have weak responses to mixed lymphocyte culture, and antigens other than MHC also contribute to immunosurveillance, this model is yet to be confirmed (Montali et al, 1998;Stone et al, 1998;Janeway et al, 2001).…”
Section: Immunology Of Dftdmentioning
confidence: 99%
“…Devil neutrophils are competent at bacterial phagocytosis and degradation, and lymphocyte proliferation can be stimulated by a variety of mitogens (Woods et al, 2007;Siddle et al, 2007a;Kreiss et al, 2008). Lymphocyte proliferation responses varied greatly between individual Tasmanian devils, and lymphocytes from animals with DFTD responded similarly to those of healthy devils (Woods et al, 2007;Kreiss et al, 2008).…”
Section: Immunology Of Dftdmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC-incompatible tumor cells transplanted from a parental strain onto an F1 hybrid showed the recipient's immune system responded against tumor cells that had not lost their MHC molecules [27]. Interestingly, Tasmanian devils maintain effective immune system and yet do not display an immune response to DFTD [28,29]. However, nude (immunodeficient) mice injected subcutaneously with DFTD cells rapidly developed tumors, indicating a lack of immunoresponsiveness enabled tumor progression [30].…”
mentioning
confidence: 99%